KERUKUNAN UMAT BERAGAMA DALAM PERSPEKTIF AGAMA BUDDHA DAN ISLAM - Sofia Hayati; Yulian Rama Pri Handiki; Heni Indrayani (Jurnal Studi Agama, 2019)
All religions teach goodness. This has become the best source for the creation of inter-religious harmony. Buddhism and Islam have noble teachings that teach goodness to mankind. Although there are also those who do not respect differences and tend to be not supporting the harmony between religion, but do not reduce the nobility of these two religions in the concept of harmony.